2012
DOI: 10.1002/maco.201206808
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural influence on corrosion properties of aluminium composites reinforced with amorphous iron borides

Abstract: Aluminium composite materials reinforced with amorphous iron borides (Fe/B) have been manufactured following a powder metallurgical (PM) route. Aluminium particles were mixed with 20% (by wt.) Fe/B particles (obtained by mechanical alloying during 36 h from iron and boron powders, 50% by wt. mixture). Mixes were uniaxially pressed and sintered at different temperatures (ranging from 650 to 1100 8C). The effect of sintering temperature on the corrosion resistance of those materials has been studied and related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…[1][2][3][4][5][6] However, they are easily penetrated and peeled owing to the corrosion destruction of their naturally formed protective surface oxide layers in seawater and solutions containing chloride ions, 4,[7][8][9] which greatly shortens their service life and even brings enormous undesirable impact in the application elds, especially for the marine industries. Till now, many methods have been developed to protect aluminum and its alloys from corrosion in seawater, such as mechanical alloying, 6,[10][11][12] electroplating coating, [13][14][15][16] brush-plating coating, 17,18 magnetron sputtering ion coating, [19][20][21] anodic oxidation, [22][23][24][25] spray deposition technology 12,26,27 and laser surface technology, [28][29][30] etc. Nevertheless, the reported approaches inevitably cause the environmental contamination and the fabricated processing is complex, high-cost and uncontrollable.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] However, they are easily penetrated and peeled owing to the corrosion destruction of their naturally formed protective surface oxide layers in seawater and solutions containing chloride ions, 4,[7][8][9] which greatly shortens their service life and even brings enormous undesirable impact in the application elds, especially for the marine industries. Till now, many methods have been developed to protect aluminum and its alloys from corrosion in seawater, such as mechanical alloying, 6,[10][11][12] electroplating coating, [13][14][15][16] brush-plating coating, 17,18 magnetron sputtering ion coating, [19][20][21] anodic oxidation, [22][23][24][25] spray deposition technology 12,26,27 and laser surface technology, [28][29][30] etc. Nevertheless, the reported approaches inevitably cause the environmental contamination and the fabricated processing is complex, high-cost and uncontrollable.…”
Section: Introductionmentioning
confidence: 99%
“…, SiC ceramic particles are cathodic sites of the coupling. Abenojar et al [16] also found that the incorporated amorphous Fe/B particles act as cathode and form a strong galvanic couple with the aluminum matrix.…”
Section: Resultsmentioning
confidence: 99%
“…One of the main challenges using Al-based MMCs is the influence of the reinforcement particles on the corrosion resistance [15,16,17,18,19]. Because adding reinforcement particles interrupts the continuity of the aluminum matrix and its protective surface oxide films, the number of sites where corrosion could be initiated increases, making the composite more susceptible to corrosion [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…PM is a technology applied to many metals, such as steel [28][29][30][31], stainless steel [32][33][34], aluminium [35,36], copper [37], titanium [38][39][40][41], and magnesium [42,43], etc. Metal powders can be pre-alloyed [44,45] or mechanically alloyed [34,46]; it depends on the application sought.…”
Section: Introductionmentioning
confidence: 99%